2010
DOI: 10.1021/jp911188r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mediator Spacing on Electrochemical and Enzymatic Response of Ferrocene Redox Polymers

Abstract: The effect of mediator distance from the polymer backbone on the redox behavior, electron transport, electrochemical stability, and electrical communication with redox enzymes was studied with novel linear poly(ethylenimine) redox polymers. To measure these effects, we synthesized two new ferrocene redox polymers having a three-carbon (Fc-C 3 -LPEI) and a six-carbon (Fc-C 6 -LPEI) spacer to complement our previous synthesized polymer (Fc-C 1 -LPEI) having a 1-carbon spacing. Increasing the spacer length to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 47 publications
3
82
0
Order By: Relevance
“…In contrast, LBL assembled (Fc-C 3 -LPEI/p-GOX) 16 biosensors are capable of generating as much, and even more, current than solution cast films. 6 When using the short wash method, the films actually surpass the current output of the previously reported glucose biosensors using the same materials. This is important for two reasons: processing time and amount of material.…”
Section: Enzymatic Response Of Lbl Assembled Biosensorsmentioning
confidence: 85%
See 3 more Smart Citations
“…In contrast, LBL assembled (Fc-C 3 -LPEI/p-GOX) 16 biosensors are capable of generating as much, and even more, current than solution cast films. 6 When using the short wash method, the films actually surpass the current output of the previously reported glucose biosensors using the same materials. This is important for two reasons: processing time and amount of material.…”
Section: Enzymatic Response Of Lbl Assembled Biosensorsmentioning
confidence: 85%
“…6 They reported that decreasing the mediator spacing between ferrocene and LPEI from six to three methylene groups increased the sensitivity, maximum enzyme response, and stability of the films. On the contrary, Mao et al reported a significant increase in electron diffusion when osmium redox centers are extended further away from the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely the case for a given hydrogel composition hydrated in a specific environment. Indeed, it has been noticed that the degree of reticulation [22,25], the nature of the enzyme and its weight percent in the hydrogel [26], the nature of the polymer [27,28], the oxidation state of its complexes [29] and the nature of the buffer (temperature, pH, ionic strength) [16,22,24,30,31] can affect the degree of hydration of the hydrogel and therefore its thickness. Since our electrodes were modified with the same hydrogel composition and were evaluated under the same experimental conditions, in the following, we assume that the hydrogel thickness increased with .…”
Section: Introductionmentioning
confidence: 99%